Rapid, Sensitive and Reliable Ricin Identification in Serum Samples Using LC–MS/MS - Feldberg, Liron (Toxins (Basel), 2021)
Ricin, a protein derived from the seeds of the castor bean plant (Ricinus communis), is a highly lethal toxin that inhibits protein synthesis, resulting in cell death. The widespread availability of ricin, its ease of extraction and its extreme toxicity make it an ideal agent for bioterrorism and self-poisoning. Thus, a rapid, sensitive and reliable method for ricin identification in clinical samples is required for applying appropriate and timely medical intervention. However, this goal is challenging due to the low predicted toxin concentrations in bio-fluids, accompanied by significantly high matrix interferences. Here we report the applicability of a sensitive, selective, rapid, simple and antibody-independent assay for the identification of ricin in body fluids using mass spectrometry (MS). The assay involves lectin affinity capturing of ricin by easy-to-use commercial lactose–agarose (LA) beads, following by tryptic digestion and selected marker identification using targeted LC–MS/MS (Multiple Reaction Monitoring) analysis. This enables ricin identification down to 5 ng/mL in serum samples in 2.5 h. To validate the assay, twenty-four diverse naive- or ricin-spiked serum samples were evaluated, and both precision and accuracy were determined. A real-life test of the assay was successfully executed in a challenging clinical scenario, where the toxin was identified in an abdominal fluid sample taken 72 h post self-injection of castor beans extraction in an eventual suicide case. This demonstrates both the high sensitivity of this assay and the extended identification time window, compared to similar events that were previously documented. This method developed for ricin identification in clinical samples has the potential to be applied to the identification of other lectin toxins.